2017
DOI: 10.1016/j.healthplace.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

A review of neighborhood effects and early child development: How, where, and for whom, do neighborhoods matter?

Abstract: This paper describes a scoping review of 42 studies of neighborhood effects on developmental health for children ages 0-6, published between 2009 and 2014. It focuses on three themes: (1) theoretical mechanisms that drive early childhood development, i.e. how neighborhoods matter for early childhood development; (2) dependence of such mechanisms on place-based characteristics i.e. where neighborhood effects occur; (3) dependence of such mechanisms on child characteristics, i.e. for whom is development most aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
228
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 273 publications
(244 citation statements)
references
References 100 publications
10
228
0
6
Order By: Relevance
“…The impacts of the limited support for young children can also be seen in educational attainment with only 65% of children from slum communities attend primary school, compared to 84% outside the slums [6]. This evidence supports the body of knowledge from high income countries that a child's place of residence in uences their development and health [10].…”
Section: Introductionmentioning
confidence: 68%
“…The impacts of the limited support for young children can also be seen in educational attainment with only 65% of children from slum communities attend primary school, compared to 84% outside the slums [6]. This evidence supports the body of knowledge from high income countries that a child's place of residence in uences their development and health [10].…”
Section: Introductionmentioning
confidence: 68%
“…For example, studies have demonstrated that parents' views on the quality of the physical neighbourhood and feelings of safeness have implications for children's moral development (Ball, Smetana, Sturge-Apple, Suor, & Skibo, 2017) and behavioural problems (Ma & Grogan-Kaylor, 2017). Low neighbourhood quality may be linked to cognitive development through proximal processes such as access to resources, parenting, and parental well-being (see for review, Minh, Muhajarine, Janus, Brownell, & Guhn, 2017). Furthermore, perceptions of the neighbourhood have been shown to moderate the association between family risk and child externalizing behaviours (Lima, Caughy, Nettles, & O'Campo, 2010).…”
Section: Neighbourhood Chaosmentioning
confidence: 99%
“…Later work used provincial data or samples of national data to examine the validity of the EDI as a common tool across jurisdictions for studying children's developmental trajectories and social and educational outcomes [21][22][23][24][25][26][27]. More recently, longitudinal data linkage studies have used the EDI to predict vulnerabilities in language and cognitive development [28][29][30], examine the association between child developmental health at kindergarten and later academic achievement [31][32][33], and analyze how physical and social settings (i.e., neighbourhoods) are associated with early child development [6,[34][35][36][37]. A regularly updated bibliography of published works including EDI analyses is available at: https://edi.offordcentre.com/ resources/bibliography-of-the-edi/.…”
Section: Research Using the Cannecd Database Peer-reviewed Researchmentioning
confidence: 99%